Music and Movement, Ragas and Dances: Orientalism, "Jugalbandhi, " and the Shankar Brothers. Issue 5 (19th October 2020) - Ramachandran, Aishwarya; Vertinsky, Patricia
ABSTRACT: There is a long history of collaboration within the Indian performing arts, blurring the spaces between their performance and reception. The careers of the Shankar brothers illuminate this intimacy; Ravi the sitarist and Uday the dancer represent two sides of the same coin. Both achieved success at moments of heightened Western interest in Oriental culture yet were criticized by Indian nationalists for adapting performances to suit Western tastes. While Uday could not overcome these critiques in the troubled political circumstances of the 1940s, Ravi's relationships with popular American musicians helped him become an authority in Western and Indian classical music.